Buerger Allen Exercise and Foot Massage Combination in Improving Foot Circulation in Diabetic Mellitus Patients - sugiyarto (Sahabat Publikasi Kuu, 2024)
Background: Diabetes Mellitus (DM) is one of the 10 leading causes of death in adults. This disease is characterized by high blood glucose levels (hyperglycemia) due to insulin resistance. Hyperglycemia in the long term can damage tissues, organs, the nervous system, and blood vessels. Some complications that arise due to DM include peripheral vascular disease and neuropathy. These complications disrupt lower extremity circulation, resulting in diabetic foot ulcers. If not treated properly, the degree of diabetic foot ulcers will worsen, resulting in amputations. Physical exercise, namely foot gymnastics, is important to prevent diabetic foot ulcers. The combination of Buerger Allen Exercise therapy with Foot Massage is a type of foot exercise that can be chosen to improve lower extremity circulation. Improvement of lower extremity circulation is evidenced by an improvement in the Ankle Brachial Index (ABI) value in the normal range of 0.9 - 1.2. Objective: To determine the effect of the combination of Buerger Allen Exercise therapy with Foot Massage on lower extremity circulation in DM patients. Research Method: This study used a Quasy Experiment research design with a pre-test-post-test with a control group design. The sample was 25 DM patients who were treated at the Banyuanyar Health Center. Patients are given combination of Buerger Allen Exercise therapy with Foot Massage. The sampling technique used non-probability sampling with a purposive sampling type. Results: The results of the Wilcoxon statistical test were 0.001 (p-value <0.05) Improvement in ABI values ​​ intervention group by 0.11% Conclusion: Combination of Buerger Allen Exercise Therapy with Foot Massage is effective in improving lower limb circulation.